Metallo-phthalocyanines containing thiazole moieties: Synthesis, characterization, electrochemical and spectroelectrochemical properties and sensor applications - KOCA, ATIF (ELSEVIER SCIENCE SA, 2019)
The synthesis of symmetrically tetra substituted metallophthalocyanines (MPcs) (M = Co, Zn, MnCI) bearing four 4-methoxyphenylthiazole-2-thio-units were reported. The structures of the newly synthesized molecules were proposed according to the elemental analysis, 1H NMR, FT-IR, and UV-vis spectral data. Redox active metal centers Coll; and Cl-Mnill and electropolymerizable substituents on the peripheral positions of Pc rings were preferred for the syntheses of MPcs to increase redox activity and electrochemically polymerization ability of the complexes. The redox properties of MPcs were characterized with voltammetry and in situ spectroelectrochemistry techniques. Then, MPcs were electropolymerized on glassy carbon electrodes (GCE). Finally, GCE/MPc electrodes were tested as electrochemical sensors for the detection of ascorbic acid (AA), dopamine (DA) and uric acid (UA) by using differential pulse voltammetry (DPV) technique. Voltammetric analyses indicated that GCE/CoPc electrode selectively detected DA with good sensitivity, while GCE/MnCIPc and GCE/ZnPc only detected DA and UA. This work provided a simple and easy approach for the electrode modification and selective and sensitive AA, DA and UA detections.
Keywords: Phthalocyanine; Thiazole; Electrochemistry; Spectroelectrochemistry; Sensor; Dopamine; Ascorbic acid; Uric acid; REDUCED GRAPHENE OXIDE; ASCORBIC-ACID; URIC-ACID; MANGANESE PHTHALOCYANINE; MODIFIED ELECTRODES; DOPAMINE; METALLOPHTHALOCYANINES; BEHAVIOR; NICKEL; COBALT